THE ROLE OF FOLK PEDAGOGY IN EDUCATION IN THE SPIRIT OF PHILANTHROPY - Israilov Galib Rashidovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article broadly interprets the practical views on the goals and objectives of folk pedagogy that have been formed in the life experience and lifestyle of a particular people. One of the most important characteristics of folk pedagogy is its antiquity. It was revealed that the periodization of Uzbek folk pedagogy takes into account the originality of the main qualities of the folk psyche, lifestyle and thinking.